(untitled) (CIPEEX, 2022)
SUICIDE AND DEPRESSION ARE PHENOMENA THAT PLAGUE THE COMMUNITY, CAUSE INTENSE SUFFERING AND ARE CONSIDERED AS A PUBLIC HEALTH PROBLEM. THE OBJECTIVE OF THIS STUDY IS TO EVALUATE THE CAUSAL FACTORS AND THE PROFILE OF HEALTH PROFESSIONALS AND STUDENTS WHO HAVE SUICIDAL TENDENCIES AND ARE AFFECTED BY DEPRESSION. AN EXPANDED SUMMARY WAS MADE BASED ON FIVE ARTICLES SURVEYED IN DATABASES SUCH AS PUBMED AND SCIELO IN THE PERIOD FROM 2014 TO 2018. THE LITERATURE HAS SHOWN THAT AMONG THE MAIN FACTORS ARE BURNOUT SYNDROME AND WORK OVERLOAD, IN ADDITION THE PRESSURE OF ACADEMIC DEMANDS.